2018
DOI: 10.1186/s12974-018-1086-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii alters NMDAR signaling and induces signs of Alzheimer’s disease in wild-type, C57BL/6 mice

Abstract: BackgroundAlzheimer’s disease (AD) is a progressive neurodegenerative disease associated with cognitive decline and complete loss of basic functions. The ubiquitous apicomplexan parasite Toxoplasma gondii (T. gondii) infects up to one third of the world’s population and is implicated in AD.MethodsWe infected C57BL/6 wild-type male and female mice with 10 T. gondii ME49 cysts and assessed whether infection led to behavioral and anatomical effects using immunohistochemistry, immunofluorescence, Western blotting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 77 publications
(86 reference statements)
2
89
0
1
Order By: Relevance
“…Indirect evidence from animal studies has shown that the production of Aß waxes and wanes in response to immune challenge and healthy resolution. For example, Aß deposits have been noted in wild-type mice infected with Chlamydia pneumoniae (Little et al, 2004 , 2014 ; Boelen et al, 2007 ), HSV1 (Wozniak et al, 2007 ), pseudorabies virus (Tanaka and Nagashima, 2017 ), or Toxoplasma gondii (Torres et al, 2018 ), while transgenic-AD mice infected with Porphyromonas gingivalis showed increased Aß deposition (Ishida et al, 2017 ). Notably, Aß returned to normal levels after the C. pneumoniae infection had resolved.…”
Section: Aß Has Antimicrobial Propertiesmentioning
confidence: 99%
“…Indirect evidence from animal studies has shown that the production of Aß waxes and wanes in response to immune challenge and healthy resolution. For example, Aß deposits have been noted in wild-type mice infected with Chlamydia pneumoniae (Little et al, 2004 , 2014 ; Boelen et al, 2007 ), HSV1 (Wozniak et al, 2007 ), pseudorabies virus (Tanaka and Nagashima, 2017 ), or Toxoplasma gondii (Torres et al, 2018 ), while transgenic-AD mice infected with Porphyromonas gingivalis showed increased Aß deposition (Ishida et al, 2017 ). Notably, Aß returned to normal levels after the C. pneumoniae infection had resolved.…”
Section: Aß Has Antimicrobial Propertiesmentioning
confidence: 99%
“…Cytokines including IL--6 and TNFα, that are characteristic of neuroinflammation, reduce the clearance of misfolded proteins such as Aβ and tau [44, 78--80]. T. gondii infection, which also results in elevated IL--6 and TNFα, induces Aβ deposition and tau hyperphosphorylation that are associated with behavioral deficits in mice [25,38]. Interestingly, one mechanism by which T. gondii evades clearance is by inhibiting autophagy [81,82], and suppression of autophagy is sufficient to induce neurodegeneration [83,84].…”
Section: Discussionmentioning
confidence: 99%
“…A previous comprehensive systems analysis found that T. gondii infection modified pathways involved in epilepsy and neurodegenerative diseases [219], and a recent meta-analysis concluded that T. gondii infection is a risk factor for AD [220]. There is also preclinical evidence suggesting that T. gondii infection promotes the development of epilepsy and AD in rodents [208,221,222]. On the other hand, a case-controlled study involving 99 epilepsy patients and 99 patients without epilepsy found no association between T. gondii infection and epilepsy [223].…”
Section: Functional Consequences Of T Gondii Infectionmentioning
confidence: 99%